Interprovincial Migration in Canada as a Human Capital Decision - Laber, Gene; Chase, Richard X. (Journal of Political Economy, 1971)
This paper develops an "economic opportunities model" of interprovincial labor movements in Canada. Viewing migration as a decision to invest in human capital, we postulate that migration flows are directly related to net present values of the investment decisions. A regression equation derived from the theoretical model contains two independent variables–the expected value of earnings differentials and a distance variable. Cross-section regression results are reported for each of ten provinces, but statistical considerations led to grouping the data into four multiprovince regions. Despite their essential simplicity, the four equations yield highly significant results, accounting for about one-half to two thirds of the variation in interprovincial migration.